The perception of creative classroom climate in elementary school students: Comparison between regular and enriched visual art classes. (2nd January 2022) - Licul, Nina; Juriševič, Mojca
ABSTRACT: Creative classroom climate has an impact on the development of gifted students, but there is still not enough empirical evidence to support this hypothesis. The purpose of this study was to examine how elementary school students, aged 11 to 14 years, experience a creative environment in different educational settings. Specifically, the aim of the study was twofold: (1) to compare gifted students' perception of creative climate in regular vs. enriched art classes, and (2) to compare the gifted students' perception of creative climate in regular art classes with the perception of their nongifted classmates. The data were collected by using an adapted version of Péter-Szarka et al. questionnaire, which measures creative climate. The results reveal that gifted students found enriched classes more creative than regular classes. The perception of the overall creative climate in regular classes was similar in both groups of students; however, in three of the five measured dimensions of creative climate the results did point to statistical and practical significance in differences between the groups. The findings of this study offer a valuable insight into the students' perception of a creative environment in art classes and may provide guidelines for enhancing the quality of gifted student education.